Electric and Magnetic Properties of Sputter Deposited BiFeO3 Films. (18th November 2013) - Siadou, N.; Panagiotopoulos, I.; Kourkoumelis, N.; Bakas, T.; Brintakis, K.; Lappas, A.
Abstract : Polycrystalline BiFeO3 films have been magnetron sputter deposited at room temperature and subsequently heat-treated ex situ at temperatures between 400 and 700°C. The deposition was done in pure Ar atmosphere, as the use of oxygen-argon mixture was found to lead to nonstoichiometric films due to resputtering effects. At a target-to-substrate distance d = 2 ′ ′ the BiFeO3 structure can be obtained in larger range process gas pressures (2–7 mTorr) but the films do not show a specific texture. At d = 6 ′ ′ codeposition from BiFeO3 and Bi2 O3 has been used. Films sputtered at low rate tend to grow with the (001) texture of the pseudo-cubic BiFeO3 structure. As the film structure does not depend on epitaxy similar results are obtained on different substrates. A result of the volatility of Bi, Bi rich oxide phases occur after heat treatment at high temperatures. A Bi2 SiO5 impurity phase forms on the substrate side, and does not affect the properties of the main phase. Despite the deposition on amorphous silicon oxide substrate weak ferromagnetism phenomena and displaced loops have been observed at low temperatures showing that their origin is not strain. Ba, La, Ca, and Sr doping suppress the formation of impurity phases and leakage currents.